Press-konferentsiia predsedatelia Konstitutsionnogo suda Rossii . Press-konferentsiia predsedatelia Konstitutsionnogo suda Rossii . Press Conference with the Chairman of the Constitutional Court of Russia . Пресс-конференция председателя Конституционного суда России - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Press conference on the "Case of the Communist Party," attended by Russian and foreign journalists and the chairman of the Constitutional Court, Valerii Zorkin. Пресс-конференция российских и иностранных журналистов с председателем Конституционного суда Валерием Зорькиным о рассмотрении "дела о КПСС.".